Novel tacrine/acridine anticholinesterase inhibitors with piperazine and thiourea linkers - Hamulakova, Slavka; Imrich, Jan; Janovec, Ladislav; Kristian, Pavol; Danihel, Ivan; Holas, Ondrej; Pohanka, Miroslav; Böhm, Stanislav; Kozurkova, Maria; Kuca, Kamil (International journal of biological macromolecules, 2014)
A new series of substituted tacrine/acridine and tacrine/tacrine dimers with aliphatic or alkylene-thiourea linkers was synthesized and the potential of these compounds as novel human acetylcholinesterase (hAChE) and human butyrylcholinesterase (hBChE) inhibitors with nanomolar inhibition activity was evaluated. The most potent AChE inhibitor was found to be homodimeric tacrine derivative 14a, which demonstrated an IC50 value of 2 nM; this value indicates an activity rate which is 250-times higher than that of tacrine 1 and 7500-times higher than 7-MEOTA 15, the compounds which were used as standards in the study. IC50 values of derivatives 1, 9, 10, 14b and 15 were compared with the dissociation constants of the enzyme-inhibitor complex, Ki1, and the enzyme-substrate-inhibitor complex, Ki2, for. A dual binding site is presumed for the synthesized compounds which possess two tacrines or tacrine and acridine as terminal moieties show evidence of dual site binding. DFT calculations of theoretical desolvation free energies, ΔΔGtheor, and docking studies elucidate these suggestions in more detail.
Keywords: aktivace enzymů; Butyrylcholinesterase; Thiourea; butyrylcholinesterasa; Acetylcholinesterase; molekulární konformace; Acridines; Enzyme Activation; akridiny; piperaziny; vazba proteinů; lidé; thiomočovina; Molecular Conformation; Models, Molecular; takrin; Tacrine; molekulární modely; acetylcholinesterasa; Piperazines; cholinesterasové inhibitory; Cholinesterase Inhibitors; Protein Binding; Humans